Transpose the unknown terms to the first member, and the known terms to the second. Unite the similar terms, and divide both members by the coefficient of the unknown quantity. A College Algebra - Page 114by Henry Burchard Fine - 1904 - 595 pagesFull view - About this book
| Charles Davies - Algebra - 1859 - 299 pages
...an equation to the other, if the sign be changed. 105. What is transposition ? EXAMPLES. Transpose **the unknown terms to the first member, and the known terms to the second,** in the following : 1. 3ж 4- 6 — 5 = 1x — 7. Ans. ux — 2x — — 7 6 4- 5. 2. ax + b = d —... | |
| Benjamin Greenleaf - 1863 - 324 pages
...the signs of all the terms of an equation may be changed, without destroying the equality. Transpose **the unknown terms to the first member, and the known terms to the second,** in the following EXAMPLES. 3. 2x — a = 6. Ans. 2ж = af-6. 4. llx-f-9 = 6ж-f-34. Ans. 11 x — 6... | |
| Horatio Nelson Robinson - Algebra - 1863 - 420 pages
...all the other terms be changed ; (3). EXAMPLES FOR PRACTICE. In the following equations, transpose **the unknown terms to the first member, and the known terms to the second,** by (I). 1. a'x-\-bc = ab — 'Lax. Ans. с?х-\-Чах = ab — be. 2. 36'— 2ж— 5 = Во— Ьах—... | |
| Benjamin Greenleaf - Algebra - 1864 - 394 pages
...x is verified. Hence the following RULE. Clear the equation of fractions, if it has any. Transpose **the unknown terms to the first member, and the known terms to the second** member, and reduce each member to its simplest form. Divide both members by the coefficient of the... | |
| Horatio Nelson Robinson - Algebra - 1864 - 420 pages
...of au the terms simultaneously ; (3). EXAMPLES FOR PRACTICE. In the following equations, transpose **the unknown terms to the first member, and the known terms to the second,** by (I). 1. cfx+lc = ab— 2ax. Ans. a'x-\-2ax = ab — be. 2. 34'— 2z-5 = 3c—5ax—dx. Ans. bax+dx—2x... | |
| Horatio Nelson Robinson - Algebra - 1866 - 312 pages
...the other member with its sign changed. EXAMPLES FOR PRACTICE. In the following equations transpose **the unknown terms to the first member, and the known terms to the second.** 3. 3x + m = b. Ans. 3x = 6 — m. 4. 4r = 2x + cd. Ans, 4x — 2x = cd. 5. 3m+l2x — c = x + d. Ans.... | |
| ELIAS LOOMIS, L.L.D. - 1868
...transposing every term in each member of the equation. EXAMPLES. In the following examples, transpose **the unknown terms to the first member and the known terms to the second** member. 1. 5^+12^3^+18. Ans. 5cc~3x=18-12. 2. 4o;-7=21-3sc. Ans. 3. 2cc-15 = ~7x+30. Ans. 4. ax+bc=... | |
| Elias Loomis - Algebra - 1873 - 360 pages
...transposing every term in each member of the equation. EXAMPLES. In the following examples, transpose **the unknown terms to the first member and the known terms to the second** member. 1. 5z+12=3x+18. Arts. 5x-3x=18-12. 2. 4x-7=21-3x. Ans. 4x+3x=2t+7. 3. 2z-15 = -7x+30. Ans.... | |
| William Guy Peck - Algebra - 1875 - 331 pages
...fractious, and performing indicated operations, we have, 6^ — 18x + 60 = 72 — 8z 3 + lGx> + 16z + 4; **transposing the unknown terms to the first member, and the known terms to the second** member, we have, 6^2 + 8z 2 — 1Gx> — 18x - 1Gx = 72 + 4 — 60 ; factoring and reducing, we have,... | |
| Horatio Nelson Robinson - Algebra - 1875 - 318 pages
...the other member with its sig.v changed. EXAMPLES FOR PRACTICE. In the following equations transpose **the unknown terms to the first member, and the known terms to the second.** 3. 3x + m = b. Ans. 3x — b — m. 4. 4z = 2x + cd. Ans. ix — 2x = cd. 5. 3m + 12x — c = x + d.... | |
| |